Cyclic plastic behaviour of 7075 aluminium alloy - Nogueira, F. de Moura (2020)
This paper aims at studying the cyclic plastic behaviour of the 7075-T651 aluminium alloy under fully-reversed strain-controlled conditions. Tests are conducted under strain-control mode, at room temperature, in a conventional servo-hydraulic machine, from smooth samples, using the single step method, with strain amplitudes (/2) in the range ±0.5 to ±2.75%. This material has exhibited a mixed behaviour, i.e. cyclic strain-hardens at higher strain amplitudes (/2/>1.1%) and cyclic strain-softens at lower strain amplitudes (/2<1.1%). A linear relationship between the degree of cyclic strain-hardening and the strain amplitude has been established for higher strain amplitudes. Fatigue-ductility and fatigue-strength properties agree with those found in the open literature for the same loading conditions